2018
DOI: 10.1021/acs.orglett.8b01016
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Reagent for UV/vis Absorbing Azobenzene-Based Quantitative Analysis of the Extent of Functional Group Immobilization on Silica

Abstract: A methallylsilane coupling reagent, containing both a N-hydroxysuccinimidyl(NHS)-ester group and a UV/vis absorbing azobenzene linker undergoes acid-catalyzed immobilization on silica. Analysis of the UV/vis absorption band associated with the azobenzene group in the adduct enables facile quantitative determination of the extent of loading of the NHS groups. Reaction of NHS-groups on the silica surface with amine groups of GOx and rhodamine can be employed to generate enzyme or dye-immobilized silica for quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The absorbance at 260 nm was thought to be the sum of the contributions from chlorine dioxide, 35 the branched chain of APO 36 and benzoquinone. However, since APO was completely converted under conditions with excess chlorine dioxide, this absorbance is likely a result of the benzoquinone intermediates and chlorine dioxide.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance at 260 nm was thought to be the sum of the contributions from chlorine dioxide, 35 the branched chain of APO 36 and benzoquinone. However, since APO was completely converted under conditions with excess chlorine dioxide, this absorbance is likely a result of the benzoquinone intermediates and chlorine dioxide.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, various functional groups such as halides, aldehydes, cyanides, and azides, which are preinstalled on allylsilanes, are grafted on the surface of silica and further applied to the incorporation of a desired biomolecule onto the silica by bioorthogonal reactions. For example, Jun et al 8 demonstrated that methallylsilanes containing NHS-ester groups were integrated on silica surfaces in the presence of Sc(OTf) 3 to afford NHS-ester functionalized silica, which allowed the immobilization of glucose oxidase on silica via amide formation (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%